Preliminary analysis on food intolerances of 88, 436 healthy people to 14 kinds of foods. Issue 5 (3rd June 2019) - Zheng, Yansong; Zhang, Liping; Zeng, Qiang; Han, Chaojin
Abstract : Purpose: Functional disorders caused by food intolerance (FI) are prevalent, thus it is important to analyze the FI of healthy people to common foods so as to guide the people for eating the healthy foods. The paper aims to discuss this issue. Design/methodology/approach: In total, 88, 436 healthy persons including 60, 902 males and 27, 534 females at the age ranging from 20 to 70 years old were subjected a normal physical examination. In total, 14 kinds of food-specific IgG antibodies were detected by enzyme-linked immunesorbent assay. Findings: The total positive rate of 14 FIs was as high as 64.16 percent. Five kinds of foods (egg, crab, cod, shrimp and milk) accounted for 84.51 percent of the total positive rate. In more than one kind of FIs, egg took the largest proportion than the others and the proportion was 58.54 percent. The second was crab with a positive rate of 56.19 percent. The antibody positive rate of any food in one kind of FIs was significantly lower than that in more than one kind of FIs ( χ 2 =629.35, p <0.001). Also, younger age subjects displayed the higher positive rate than the older age groups. In addition, there was no significant difference on FI between male and female subjects. Originality/value: The results would not only prompt us to pay more attention to FI in daily life, but provide theoretical foundation for the early prevention, diagnosis and treatment of related clinical diseases as well as guiding people healthy meals.